Thermal behaviour of binuclear cyclopalladated compounds containing anionic azo-ligands - Almeida, E. T. de; Mauro, A. E.; Santana, A. M. (Editora Unesp, 2002)
This paper deals with the thermal behavior study of cyclopalladated complexes obtained from reactions of [Pd(dmba)N-3](2) (1), dmba = N,N-dimethylbenzylamine, with azole-compunds, such as, the anionic ligands pyrazolate (pz), imidazolate (imz) and 3,5-dimethyl-pyrazolate (3,5-dmpz), The characterization of the binuclear complexes [Pd(dmba)(mu-pz)](2) (2), [Pd(dmba)(mu-imz)](2) (3) and [Pd(dmba)(mu-3.5-dmpz)](2) (4) was carried out by elemental analysis, IR and NMR spectroscopy, Their thermal behaviour has been investigated and the final product was identified by X-ray powder diffractometry which showed the formation of Pd(0) as final decomposition product.
Keywords: cyclopalladated; thermal analysis; pyrazolate; imidazolate; 3,5-dimethyl-pyrazolate